Understanding indirect users' privacy concerns in mobile forensics — A mixed method conjoint approach - Hildebrandt, Julian Romeo; Schomakers, Eva-Maria; Ziefle, Martina; Calero Valdez, André (Frontiers in Computer Science, 2023)
The advent of mobile forensics toolkits introduces a technological leverage that allows legal authorities to access information stored on mobile devices, thus shining a new light on law enforcement procedures. These pocket-sized devices, mobile phones, accumulate a plethora of user data, effectively becoming a beacon for individual identification. However, the prospect of exploring this data within a criminal inquiry raises palpable concerns about potential privacy encroachments. Consequently, there exists an urgent need to balance the instrumental value of these technologies with their potential to intrude upon privacy, ensuring a framework that remains legally and ethically sound. In our study, we offer a contemplative view on the public reception of such measures, informed by interviews and a conjoint study conducted across two representative cohorts from Germany and Austria (n=2040). Our analysis indicates a marked preference for the release of geo-spatial data over more personal content, such as photographs. Additionally, respondents showed a higher acceptance for automated analysis in comparison to human manual evaluation. The divergence between the two countries was negligible. In summary, despite the inherent concerns, the use of these mobile forensics tools demonstrated a high degree of public acceptance.